PREFERENSI MUSIK DAN KECERDASAN EMOSI MAHASISWA PROFESI NERS UNIVERSITAS KLABAT - Grace Fresania Kaparang; Mega Gayo (Fakultas Ilmu Keperawatan Universitas Klabat, 2020)
Emotional intelligence is crucial in life; thus, proper stimulations, including music, were necessary. The study aimed to identify the relationship between music preference and emotional intelligence and also to find if there is any significant difference in emotional intelligence among music preference groups. Descriptive correlational method with cross-sectional approach and purposive sampling technique were employed. Most of the students prefer unpretentious music genres and having